Comparison of the sugar and organic acid components of seventeen table grape varieties produced in Ankara (Türkiye): a study over two consecutive seasons - Kunter, Birhan; Unal, Osman Batur; Keskin, Sıddık; Hatterman-Valenti, Harlene; Kaya, Ozkan (Frontiers in Plant Science, 2024)
Sugars and organic acids not only have a significant impact on taste balance and sensory acceptance by consumers but also play a crucial role in the chemical equilibrium of grape juices and wines. Therefore, this study aimed to quantify the content and composition of sugars and organic acids in 17 grape varieties over two consecutive years using high-performance liquid chromatography. The variability in all the parameters studied was strongly influenced by both the grape cultivars and specific years (p ≤ 0.05). In grape berries, the primary sugars identified were fructose and glucose, which ranged from 6.50 to 11.10 g/L and from 5.83 to 12.12 g/L, respectively, over the two years. However, sucrose was not detected in any of the grape varieties examined. For the two respective years, the highest titratable acidity (TA) was found in Tekirdağ Çekirdeksizi (TeCe) (0.89 and 0.90 g/L), while the lowest was detected in Victoria (Vi) (0.48 and 0.51 g/L). Total soluble solids (TSS) peaked in Horoz Karası (HoKA) (21.90 °Brix), whereas it reached its lowest point in Big Perlon (BiPe) (14.1 °Brix). The tartaric acid content in the grape berries, ranging from 1.48 to 10.33 g/L for the two years, exhibited similar characteristics to malic acid, which ranged from 1.09 to 9.62 g/L and from 1.03 to 9.68 g/L for the two respective years. The succinic, malic, tartaric, citric, and oxalic acid contents were notably higher in the Kyoho (Ky) variety than in the other varieties. When examining the dendrogram of the contents of organic acid and sugar for similarities, it was evident that 16 out of the 17 grape varieties had a high degree of similarity, except for Alphonse Lavallée (AlLa) and HoKa. The similarity levels among the varieties ranged from 99.49% to 72.36%. The highest similarity (99.49%) was observed between the AlLa and Barış (Ba) varieties. The lowest similarity was observed among the AlLa, HoKa, and Ky varieties. In summary, this study underscores that certain table grape varieties grown in Ankara exhibit significant variations in valuable organic acids and sugars, which are associated with potential health benefits when considering human consumption.